Associations between population density and clinical and sociodemographic factors in women living with HIV in the Southern United States. Issue 2 (1st February 2021) - Edmonds, Andrew; Haley, Danielle F.; Tong, Weiqun; Kempf, Mirjam-Colette; Rahangdale, Lisa; Adimora, Adaora A.; Anastos, Kathryn; Cohen, Mardge H.; Fischl, Margaret; Wilson, Tracey E.; Wingood, Gina; Konkle-Parker, Deborah
ABSTRACT: To explore the associations of urbanicity with clinical/behavioral outcomes and sociodemographic factors among women living with HIV in the Southern United States, 523 participants of the Women's Interagency HIV Study were classified into population density quartiles. Rural-Urban Commuting Area codes revealed that 7% resided in areas where >30% commute to urban areas, 2% resided in small towns or rural areas, and 91% resided in varying densities of urban areas. Although women in lower density, mostly suburban areas reported higher socioeconomic indicators such as advanced education and greater annual household income, larger proportions of women in the lowest density quartile perceived discrimination in health care settings and agreed with several internalized HIV stigma scale items. Women in the lower quartiles had higher CD4 counts, while those in the lowest quartile were more likely to have a suppressed HIV viral load, report being employed, and not report a history of drug use or current heavy alcohol use. More research is needed to understand the interplay between population density and mechanisms contributing to HIV control as well as increased internalized stigma and perceived discrimination, along with how to target interventions to improve outcomes for individuals with HIV across urban, suburban, and rural areas.